149P Revamping the ovarian tumour microenvironment with an oncolytic adenovirus yields enhanced tumour-infiltrating lymphocyte anti-tumour activity. (15th December 2019) - Santos, J M; Heiniö, C; Cervera-Carrascon, V; Siurala, M; Quixabeira, D C A; de Gruijl, T; Lassus, H; Kanerva, A; Hemminki, A
Abstract: Background: The ovarian tumour microenvironment is an abundant source of tumour-infiltrating lymphocytes (TILs) which can be readily harnessed for infusion in the context of adoptive TIL therapy. This strategy has been proven feasible, but it appears clinically ineffective in ovarian cancer patients due to the absence of tumour-reactive TILs and the presence of immunosuppression. Hence, we hypothesized that an oncolytic adenovirus expressing Tumour Necrosis Factor (TNF)-alpha(a) and Interleukin (IL)-2 (Ad5/3-E2F-D24-hIL-2-IRES-TNFa; TILT-123) could overcome this by generating a proinflammatory microenvironment and reinvigorating TIL anti-tumour activity. Methods: Fresh explants from metastatic or primary tumour sites were obtained from stage III-IV ovarian cancer patients and short-term cultures were established in the absence or presence of oncolytic adenovirus. The remainder of the tumour explant was used to generate clinically relevant TILs which were co-cultured with autologous T cell-depleted single cell suspensions pre-treated with or without oncolytic adenoviruses. Cytokine content changes and TIL reactivity was assessed during culture by flow cytometry or interferon (IFN) gamma(g) enzyme-linked immune sorbent assay. Results: Treatment of short-term cultures with oncolytic adenovirus coding for TNFa and IL-2 introduced profound changes within the microenvironment, which were characterized by an increase in proinflammatory cytokines and decrease in suppressive cytokines. Further benefits were seen in T-cell depleted ovarian cancer single-cell suspensions infected with cytokine-coding oncolytic adenovirus, which enabled significant production of IFNg by autologous TILs. Such levels were not seen in co-cultures where no virus or the backbone oncolytic adenovirus (no cytokine transgenes) was added. Conclusion: These data illustrate the potential of oncolytic adenovirus coding for TNFa and IL-2 to rewire the ovarian tumour microenvironment for effective TIL anti-tumour reactivity. This approach may improve the efficacy of adoptive TIL therapy in ovarian cancer patients, thus warranting further clinical investigation. Legal entity responsible for the study: TILT Biotherapeutics Ltd. Funding: TILT Biotherapeutics Ltd. Disclosure: J.M. Santos: Full / Part-time employment: TILT Biotherapeutics Ltd. V. Cervera-Carrascon: Full / Part-time employment: TILT Biotherapeutics Ltd. M. Siurala: Full / Part-time employment: TILT Biotherapeutics Ltd. T. de Gruijl: Advisory / Consultancy: TILT Biotherapeutics Ltd. A. Hemminki: Shareholder / Stockholder / Stock options, Full / Part-time employment, Officer / Board of Directors: TILT Biotherapeutics Ltd. All other authors have declared no conflicts of interest.